Water Harvesting Based Integrated Vertical Farming - Sahu, R K; Pali, A K; Sinha, J (Journal of Agricultural Engineering, 2011)
Water shortage at critical times is a dominant constraint in most rain fed areas. Small Farm Reservoir (SFR) could play an important role in alleviating the problem by mitigating drought situation and/or submergence in these areas. It has multiple uses such as reducing drainage congestion, irrigation and aquaculture, improved cropping systems, increasing productivity and income, harnessing idle farm labour and improving family nutrition, although the utilization of full potential of SFR depends on innovativeness of the owner. To address the main issue of the farmers who do not wish to loose 5 to 20% land forever, it is imperative to consider integrated vertical farming to have multifarious uses of the same land/water. The multi-storeyed farming and animal rearing on the bunds of SFR is one of the options. The stored water of SFR can be used for fish (below water surface) and duck rearing (on the water surface) and space above it for poultry and rabbit farming. This system has great potential to boost the economy of farmers. The excreta of rabbits and poultry birds served as a part of the fish-food as well as add value to the stored water. Besides the animal rearing practiced on peripheral bunds would produce good amount of dung and urine, which was sloped down to SFR water which further helped to provide feed and value addition to the water. This organic water through drip irrigation system was used to irrigate orchards grown in the vicinity of SFR. The B:C ratio of such a system varied from 5.08 to 6.17 depending upon the intensity of remunerative activities. This paper reviews some of the systems installed at various places in the country to bring out the practical applications. It is concluded that in view of the decreasing trend in the average land holdings, innovative forms of this technology could be used by adding suitable components to enhance the farmer’s income